2017
DOI: 10.1038/s41598-017-14389-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin interaction networks revealed unique connectivity patterns of broad H3K4me3 domains and super enhancers in 3D chromatin

Abstract: Broad domain promoters and super enhancers are regulatory elements that govern cell-specific functions and harbor disease-associated sequence variants. These elements are characterized by distinct epigenomic profiles, such as expanded deposition of histone marks H3K27ac for super enhancers and H3K4me3 for broad domains, however little is known about how they interact with each other and the rest of the genome in three-dimensional chromatin space. Using network theory methods, we studied chromatin interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 37 publications
(64 reference statements)
5
42
0
Order By: Relevance
“…Interestingly, the H3K4me3 writer MLL4 is essential for the maintenance of both H3K4me3-BDs and super-enhancers, but not for narrow-peak promoters and standard enhancers (Dhar et al 2018). Initially, a strong emphasis was placed on the distinction between H3K4me3-BDs and super-enhancers (Benayoun et al 2014) even if they were later shown to be close or sometimes overlapping in the linear genome (Cao et al 2017) and in 3D (Thibodeau et al 2017). Whilst super-enhancers may be responsible for generating broad domains very few studies have addressed the length and maintenance of these regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the H3K4me3 writer MLL4 is essential for the maintenance of both H3K4me3-BDs and super-enhancers, but not for narrow-peak promoters and standard enhancers (Dhar et al 2018). Initially, a strong emphasis was placed on the distinction between H3K4me3-BDs and super-enhancers (Benayoun et al 2014) even if they were later shown to be close or sometimes overlapping in the linear genome (Cao et al 2017) and in 3D (Thibodeau et al 2017). Whilst super-enhancers may be responsible for generating broad domains very few studies have addressed the length and maintenance of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Super-enhancers were originally defined as enhancers with unusually high levels of certain transcriptional co-activators (Whyte et al 2013; Lovén et al 2013) and a median size larger than 8 kb (Pott and Lieb 2015). Recent studies of 3D genome networks suggest that the presence of H3K4me3-BDs in genes is associated with increased interactions with active super-enhancers (Cao et al 2017; Thibodeau et al 2017). More recently, Dhar and co-workers have shown that the histone methyl-transferase, MLL4, is essential for the methylation of both super-enhancers and H3K4me3-BDs, and proposed a hypothetical model whereby MLL4 would be essential to maintain the interaction of super-enhancers and tumour-suppressor genes with BDs (Dhar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in contact maps from numerous primary human tissues and cell types, a subset of regions rich in strong enhancer clusters (“LCRs/super‐enhancers”) and active genes were seen interacting unusually frequently. These co‐interacting regions, called “FIREs”, display tissue specificity, only partially involve CTCF and cohesin binding, and are thus central to the conformation of the active compartment in the different cell types (Schmitt et al , ; Thibodeau et al , ). This finding was confirmed by an orthogonal, ligation‐free, approach called GAM (“genome architecture mapping”; Beagrie et al , ).…”
Section: Transcription As a Looping Forcementioning
confidence: 99%
“…Unusually large regions of the H3K4me3 mark have been observed in multiple cell types across humans, mice, and other species, often spanning up to 60 kb (Adli et al 2010;Benayoun et al 2014;Chen et al 2015). Importantly, the broadest 5% of H3K4me3 domains were found to mark genes with cell type-specific functions (Benayoun et al 2014;Thibodeau et al 2017). These regions have been termed broad domains ( Figure 1D).…”
mentioning
confidence: 99%
“…These regions denote important classes of regulatory elements, which show cell type specificity, transcriptional activity in reporter assays, and disease relevance based on GWAS SNP enrichments (Kvon et al 2012;Hnisz et al 2013Hnisz et al , 2015Parker et al 2013;Benayoun et al 2014;Boyle et al 2014;Blinka et al 2016;Lin et al 2016;Dave et al 2017). Few studies have compared the characteristics for subsets of these annotations, showing some degree of overlap between HOT regions and super enhancers (Li et al 2016), and chromatin interactions between broad domains and super enhancers (Thibodeau et al 2017). However, the functional differences among these annotations, especially how genetic variation in these elements affects target gene expression, are unclear.…”
mentioning
confidence: 99%